2020
DOI: 10.3389/fimmu.2020.00714
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Impact of Daclizumab Beta on Circulating Natural Killer Cells by Mass Cytometry

Abstract: Daclizumab beta is a humanized monoclonal antibody that binds to CD25 and selectively inhibits high-affinity IL-2 receptor signaling. As a former treatment for relapsing forms of multiple sclerosis (RMS), daclizumab beta induces robust expansion of the CD56 bright subpopulation of NK cells that is correlated with the drug's therapeutic effects. As NK cells represent a heterogeneous population of lymphocytes with a range of phenotypes and functions, the goal of this study was to better understand how daclizumab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Interestingly, recent data from trials of various MS drugs such as IFN-β, fingolimod, and daclizumab indicate that the size of NK cell populations-specifically CD56 bright cells-is increased upon treatment (167,168). A mass cytometry-based investigation of circulating CD56 bright cells in patients with RR-MS treated with daclizumab beta revealed an upregulation of CD56 in total NK cells along with multiple phenotypic changes in the CD56 bright cell population (169). One study examining the roles and biological features of CD27 high and CD27 low/− NK cells during the pre-disease onset stage in EAE found that the numbers of CD27 low/− NK cells in the spleen, lymph nodes, and bone marrow were increased whereas the number of CD27 high cells was decreased; this was accompanied by enhanced cytotoxicity of CD27 low/− NK cells and reduced IFN-γ production of CD27 high NK cells.…”
Section: Nk Cells and Multiple Sclerosismentioning
confidence: 99%
“…Interestingly, recent data from trials of various MS drugs such as IFN-β, fingolimod, and daclizumab indicate that the size of NK cell populations-specifically CD56 bright cells-is increased upon treatment (167,168). A mass cytometry-based investigation of circulating CD56 bright cells in patients with RR-MS treated with daclizumab beta revealed an upregulation of CD56 in total NK cells along with multiple phenotypic changes in the CD56 bright cell population (169). One study examining the roles and biological features of CD27 high and CD27 low/− NK cells during the pre-disease onset stage in EAE found that the numbers of CD27 low/− NK cells in the spleen, lymph nodes, and bone marrow were increased whereas the number of CD27 high cells was decreased; this was accompanied by enhanced cytotoxicity of CD27 low/− NK cells and reduced IFN-γ production of CD27 high NK cells.…”
Section: Nk Cells and Multiple Sclerosismentioning
confidence: 99%
“…This may be a key regulatory mechanism to control overt T effector cell proliferation and activation in response to local IL-2 production at the sites of inflammation and is consistent with the higher proportion of CD56 br NK cells in tissues compared to circulation [ 37 ]. A regulatory role for CD56 br NK cells has been previously suggested in the context of multiple sclerosis patients treated with anti-CD25 (daclizumab) [ 38 , 39 ]. Response to treatment in these patients was associated with a significant expansion of CD56 br NK cells and concomitant decline in the frequency of both CD4 + and CD8 + T cells in blood, thereby supporting a regulatory role of CD56 br NK cells via NK cell-mediated negative immunoregulation of activated T cells.…”
Section: Discussionmentioning
confidence: 99%
“…CD38+ NK cells may impose regulatory functions in MS, as CD38+CD56bright NK cells are implicated in adenosine production, which consequently inhibits autologous CD4+ T cell proliferation 22 . Interestingly, the anti-CD25 monoclonal antibody daclizumab increases CD38 expression by CD56bright NK cells 27 . Moreover, CD38 characterizes mature NK cells, which demonstrate efficacious cytokine production and cytolytic functions 28 .…”
Section: Discussionmentioning
confidence: 99%